Spatial analysis of the French Pleistocene permafrost by a GIS database. (3rd September 2015) - Andrieux, Eric; Bertran, Pascal; Saito, Kazuyuki
Abstract: GIS analysis of the French database of Pleistocene periglacial features allows an improved evaluation of the maximum extent of past permafrost. The distribution of typical ice‐wedge pseudomorphs does not extend south of 47°N and therefore suggests that widespread discontinuous permafrost did not affect the regions south of the Paris Basin. The exclusive presence of sand wedges with primary infill between 45 and 47°N, mainly in the periphery of coversand areas, suggests that thermal contraction cracking of the ground occurred together with sand drifting in a context of deep seasonal frost or sporadic discontinuous permafrost, unfavourable for the growth of significant ground‐ice bodies. The latitudinal variation of the wedge dimensions clearly shows that the sand wedges were located in the southern margin of the area affected by thermal contraction. The proposed map of Pleistocene permafrost in France partially reconciles field data with palaeoclimatic simulations. The remaining discrepancies may arise primarily from the time lag between the Last Permafrost Maximum ( c . 31–24 ka) and the Last Glacial Maximum (21 ka). Copyright © 2015 John Wiley & Sons, Ltd.